Control of compensation devices by synchronous reference frame and fourier control methods to improve the power quality in a microgrid - Naderipour, A. (Institute of Electrical and Electronics Engineers Inc., 2016)
The present study used passive filters (PF) and designed Active Power Filters (APFs) with two control methods: synchronous reference frame control and Fourier methods. Studies in the domain of microgrids include distributed generation sources and non-linear loads. Distributed Generation Sources (DGs) include Micro-Turbine (MT) and Fuel Cell (FC), which act as a source of harmonic currents with non-linear loads. To achieve this goal, passive filters are applied to cancel the main harmonics and to provide reactive power, whereas SAPFs are applied to adjust system imbalances and remove the remaining harmonics in the system. The results show that the method can reduce the harmonic disturbances of the system from 24.27% to less than 5%. In addition, this study analyzes how the various control methods operate on active filters. The proposed method has been validated experimentally, and the results are in agreement with the simulation results.